Knowledge, Attitudes, and Practices of the population on preventive measures against covid-19, Belém, Pará – Brazil (Research, Society and Development, 2022)
This is a population survey on Knowledge, Attitudes and Practices on preventive measures against covid-19 in the population of Belém do Pará, Brazil. Among the 381 respondents, 94,0%, 79,8% and 97,1% had knowledge, attitudes and positive practices regarding covid-19, respectively. Most were female (60,10%) and aged ≥ 60 years (75,06%), completed high school (35,43%), family income 2-3 minimum wages (37,27%); sanitized their hands (89,24%), wore a mask (88,19%) and had been vaccinated (83,20%). It was observed that male individuals, with up to 1 minimum wage, aged ≥ 70 years and who did not get sick had less knowledge about the disease. In addition, a considerable number of unvaccinated respondents did not intend to be immunized (37,50%). The data suggest that the population had knowledge about the disease and demonstrated positive attitudes and good practices in relation to covid-19. However, there is a need for public policies and continuous health education.